Selected Plant Phytobiotics Feed Additive Based on Antimicrobial Property and Application in Meat-Type Duck - Widodo, Eko (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Several herbs have been evaluated on the possible use as phytobiotics feed additive inÂ chickens, but information with regard of comparative antibacterial activity of tumeric, whitetumeric, javanese ginger and black ginger is elaborated. Attempt has been made to examineresponse performances of addition of herb extract that has the highest antibacterial activity in meattypeduck. The aims of Â research were to examine antibacterial activities on several herbs extracttowardEscherichia coli, and to find the best level of selected herb water extract use on performancesof meat-type duck. The result was expected to contribute knowledge on the use of herb waterextract for meat-type duck. The research was divided into 2 parts, in the first part was to evaluateantibacterial activity of herbs and the second part was to biologically test the use of selected herb onmeat-type duck performances. In the first experiment, there were 6 treatments namely A0 Aquadest100 %, A1 antibiotic tetracycline+ Erythromycine, A2 tumeric extract, A3 white turmeric extract, A4javanese ginger extract and A5 black ginger extractin which the responses to inhibit Escherichiacoliwere tested. Variablesmeasured were Minimum Inhibition Concentration (MIC) and MinimumBacterial Inhibitory Concentration (MBIC) testagainst Escherichia coli. The result showed that use ofturmeric extractgave highly significant on MICagainstEscherichia coli (P<0,01), further test indicatedas low as 50 % (w/v) concentration of turmeric extract was enable to showed as MBIC againstEscherichia coli. The second experiment was dealt with 5 dietary treatments (P0 (basal feed), P1(basal feed+antibiotic), P2 (basal feed+turmeric extract 0.7 ml/duck/day), P3(basal feed+turmericextract 1.4 ml/duck/day)and P4 (turmeric extract 2.1 ml/duck/day)) with oral treatment onperformances of hybrid duck. Variables in this research were feed consumption, body weight gain,feed conversion and IOFC. The result of this research showed that the use of turmeric extract withoral treatment highly significantly affected feed consumption, body weight gain and IOFC (P<0,01),significantlyaffected feed conversion ratio (P<0,05). The conclusion of this research was among theherbs selected turmeric extract showed the highest diameter of zone inhibition if challance againstEscherichia coli with MBICof 50 % (w/v), and 2.1ml/duck/day oral treatment of turmeric extractcould increase performances of meat-type duck.Key Words: Antibacterial, Turmeric Extract, Meat-Type Duck, Performances